AI in special education: opportunities and challenges for Autism and ADHD - Mohd Yunus, Sri Yusmawati; Hashim, Norhafizah; Yusof, Rozianiwati; Aziz Fadzillah, Nor Azlina; Abdul Rahman, Normaziah (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
Artificial Intelligence (AI) is transforming education, offering significant benefits for children with Autism Spectrum Disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD) by providing personalized learning that adapts to their pace, strengths, and social-emotional needs. AI can also support early diagnosis and intervention through analysis of behavioral data, speech patterns, and classroom interactions. However, while these opportunities are promising, educators, parents, and policymakers must carefully address the challenges of integrating AI to ensure it effectively meets the unique needs of special education students.